2002
DOI: 10.1080/146608202760834139
|View full text |Cite
|
Sign up to set email alerts
|

F-Waves and the corticospinal lesion in amyotrophic lateral sclerosis

Abstract: F-wave excitability is largely dependent on the size of the lower motor neuron pool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…8,20,21 F-wave persistence when compared with controls was abnormal in 23 patients with MND and decreased as MRC graded strength decreased. F-wave latencies and chronodispersion, defined as the difference between the maximal and minimal F-wave latencies, were increased in the ALS patients as compared to the controls in this study by Argyriou and colleagues.…”
Section: Peripheral Nerve Conduction Studies In Alsmentioning
confidence: 88%
“…8,20,21 F-wave persistence when compared with controls was abnormal in 23 patients with MND and decreased as MRC graded strength decreased. F-wave latencies and chronodispersion, defined as the difference between the maximal and minimal F-wave latencies, were increased in the ALS patients as compared to the controls in this study by Argyriou and colleagues.…”
Section: Peripheral Nerve Conduction Studies In Alsmentioning
confidence: 88%
“…A reduction of F‐wave persistence associated with immobility has been described, although this has not been replicated by others . Upper motor neuron lesions are associated with a higher frequency and amplitude of F‐wave responses, as observed in amyotrophic lateral sclerosis . The effect of immobility on H‐reflex responses is less well studied.…”
Section: Introductionmentioning
confidence: 94%
“…The F‐wave minimal latency was determined from recordings following 20 consecutive supramaximal stimuli at 1 H Z . A peak‐to‐peak deflection from baseline of at least 40 μV was accepted as an F wave 8, 10. At the first investigation, standard ulnar nerve conduction studies were performed below and across the elbow to exclude ulnar nerve entrapment.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study in ALS patients, we observed significant positive correlations between strength of the abductor digiti minimi muscle (ADM) and a number of neurophysiological parameters, particularly compound muscle action potential (CMAP) amplitude and area, and F‐wave frequency; in addition, a negative correlation was found with distal motor latency (DML) 8. From these data, we calculated the neurophysiological index (NI), according to the formula: (CMAP amplitude/DML) × F frequency % 8, 10. This index proved to be strongly correlated with strength 8, 10…”
mentioning
confidence: 99%
See 1 more Smart Citation